Estudo de caso de um sistema convectivo de mesoescala na cidade de Belém em setembro de 2012 - OLIVEIRA, Douglas Carvalho de (2019)
One of the most observable meteorological phenomena that affect society in general are the convective storms with heavy rainfall. From a statistical viewpoint, these intense events are those which, although not numerous, are responsible for a large percentage of the total rainfall in a given period and region, ie, are events with large amounts of rain in a short time (Xavier et al, 2007). The present work aims to expose a synoptic analysis of the city of Belem, state of Para, day 27/09/2012. That same day there was a storm that saw a cumulative rainfall of about 75 mm, causing floods in the city under study. With meteorological data surfaces (INMET), the radiosonde (CPTEC) and satellite imagery (GOES), it was around 18:00 UTC the presence of a convective system in the city of Belem.